Digitization of Land Title and Records of the Cooperative Housing Societies - ur Rehman, Munib (Journal of Applied Research and Multidisciplinary Studies, 2025)
Cooperatives are autonomous, people centered and voluntary associations of persons efficaciously addressing the common economic, social, and cultural needs and aspirations of the members, aiming at their wellbeing through collective action. These organizations work democratically, in line with Cooperative Principles & Values to meet their objectives. Cooperatives have exhibited remarkable performance in almost all sectors of economic life. In housing, Cooperatives’ contribution is significant as it added to government’s affirmation of providing shelter to the shelter-less on self-help basis without any governmental financial implication. Cooperative Department Govt of Punjab has, time and again, been introducing different interventions to strengthen the Cooperative Societies so as to make them more vibrant player in national economy. Computerization of Landtitles and Records (CLTR) of Cooperative Housing Societies in Punjab is one of such initiative to ensure transparency, efficiency and strengthening of cooperative institutions through automation of processes. The focus of present study is to evaluate the working of the CLTR in institutionalizing the transparency, efficient service delivery and effective monitoring . The study, first ever of its kind, was conducted through qualitative approach by discourse analysis (organizational documents) and by semi structured interviews. The data so collected was thematically analyzed using Nvivo v 10 which indicated that implementation of this intervention was highly welcomed and is considered as a meaningful measure for enhancement in the performance of Cooperatives Department as well as of Cooperative Housing Societies as well as ensuring strengthening of the cooperative movement and creating employment opportunities in the society.